2019
DOI: 10.18087/cardio.2019.3.10220
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Physiology and Pathophysiology: Focus on the Cardiovascular System

Abstract: Ghrelin is a multifunctional peptide hormone, mainly synthesized by P / D1 cells of the stomach fundus mucosa. Its basic effect, which is realized via GHS-R1 α receptor in the arcuate and the ventromedial nucleuses of hypothalamus, is stimulation of the synthesis of pituitary hormones. Ghrelin is involved in control of appetite and energy balance, regulation of carbohydrate and lipid metabolism, cell proliferation and apoptosis, as well as modulation of functioning of gastrointestinal, cardiovascular, pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
3
0
1
Order By: Relevance
“…In addition to stimulating appetite and regulating energy balance, ghrelin and its receptor GHS-R1a exert direct effects on the cardiovascular system, such as anti-inflammation, anti-apoptosis, inhibition of sympathetic nerve activation, regulation of autophagy, and endothelial dysfunction [4,6]. However, the molecular mechanisms underlying the effects of ghrelin on the cardiovascular system have not been fully elucidated (Figure 1), and there is no specific therapeutic agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to stimulating appetite and regulating energy balance, ghrelin and its receptor GHS-R1a exert direct effects on the cardiovascular system, such as anti-inflammation, anti-apoptosis, inhibition of sympathetic nerve activation, regulation of autophagy, and endothelial dysfunction [4,6]. However, the molecular mechanisms underlying the effects of ghrelin on the cardiovascular system have not been fully elucidated (Figure 1), and there is no specific therapeutic agent.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ghrelin is synthesized and secreted by isolated murine and human cardiomyocytes [3]. In addition to regulating metabolism and appetite, ghrelin exerts wide spread physiological effects [4]; recent research has shown a strong relationship between ghrelin and the cardiovascular system [5][6][7]. Ghrelin has demonstrated cardioprotective effects, including enhancement of the endothelial and vascular function, inhibition of the sympathetic drive, reduction in blood pressure, prevention of atherosclerosis, inhibition of cardiac remodeling after myocardial infarction (MI), and improvement in cardiac function [4,8].…”
Section: Introduction Of Ghrelinmentioning
confidence: 99%
“…Описано кардиопротективное и вазодилатирующее действие грелина. Он уменьшает проявления эндотелиальной дисфункции у лиц с метаболическим синдромом, стимулируя выработку оксида азота и активируя NO-синтазу [35]. Недавно было показано, что грелин блокирует прогрессирование НАСГ у мышей, которых кормили диетой с высоким содержанием жиров.…”
Section: грелинunclassified
“…Aortic enlargement and impaired aortic bioelastic function is a sequel of cardiac and non-cardiac diseases in children [2][3][4] . This sequel is of clinical importance as it can lead to cardiovascular complications such as left ventricular hypertrophy, aneurysmal anomalies of great vessels and myocardial infarction [5][6][7] . It is noteworthy that aortic pulse wave velocity (PWV) and aortic distensibility which correlates with the descending bioelastic function of the aorta serve as pathogenic markers in the disease of the cardiovascular disease 8 .…”
Section: Introductionmentioning
confidence: 99%